2015
DOI: 10.1104/pp.15.00549
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Variegation of Thylakoid Formation1 Is Suppressed by Mutations of Specific σ-Factors in Arabidopsis

Abstract: Thylakoid Formation1 (THF1) has been shown to play roles in chloroplast development, resistance to excessive light, and chlorophyll degradation in Arabidopsis (Arabidopsis thaliana). To elucidate mechanisms underlying THF1-regulated chloroplast development, we mutagenized thf1 seeds with ethyl methanesulfonate and screened second-site recessive mutations that suppress its leaf variegation phenotype. Here, we characterized a unique suppressor line, 42-6, which displays a leaf virescent phenotype. Map-based clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 67 publications
(120 reference statements)
1
14
0
Order By: Relevance
“…PRPS9 and PSRP5 are plastid ribosomal proteins that are second-site mutations and suppress leaf variegation of thf1-1. SIG6 is a plastid transcription factor specifically controlling gene expression through the plastid-encoded RNA polymerase and the mutation of SIG6 suppresses thf1 variegation (Hu et al 2015). Genetic screening for the second-site suppressor lines of thf1 and var2 suggested that the reduced rate of plastid protein biosynthesis is important for chloroplast development in variegated leaves (Ma et al 2015b).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…PRPS9 and PSRP5 are plastid ribosomal proteins that are second-site mutations and suppress leaf variegation of thf1-1. SIG6 is a plastid transcription factor specifically controlling gene expression through the plastid-encoded RNA polymerase and the mutation of SIG6 suppresses thf1 variegation (Hu et al 2015). Genetic screening for the second-site suppressor lines of thf1 and var2 suggested that the reduced rate of plastid protein biosynthesis is important for chloroplast development in variegated leaves (Ma et al 2015b).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…2), are detected in the green but not the white leaf areas, specifically in the chloroplasts, of the var2 mutant grown even under normal light conditions, indicative of its persistent photooxidative stress (Kato et al, 2009). A series of genetic studies in Arabidopsis identified trans-acting factors suppressing var1/var2 leaf variegation; these included Clp subunits, translation factors, a pentatricopeptide repeat protein, a pseudouridine synthase homolog, a plastid transcriptionally active chromosome component, a prokaryotic-like peptide deformylase, ribosomal proteins, circularly permuted GTPase family proteins, and a sigma factor Miura et al, 2007;Yu et al, 2008Yu et al, , 2011Liu et al, 2010aLiu et al, , 2010bLiu et al, , 2013Adam et al, 2011;Wu et al, 2013;Powikrowska et al, 2014;Hu et al, 2015;Ma et al, 2015;Qi et al, 2016). Several models have been proposed to explain leaf variegation suppression, but the precise mechanism remains elusive (Miura et al, 2007;Yu et al, 2008).…”
Section: Ftshmentioning
confidence: 99%
“…The absence of thylakoid FtsH2/5 (but not FtsH1/8) induces variegated leaf phenotype (Sakamoto et al, 2003;Zhang et al, 2010), probably independent of D1 degradation . The leaf variegation is suppressed by defects in the gene expression apparatus, translation machineries, or other protease components in the chloroplast (Park and Rodermel, 2004;Miura et al, 2007;Yu et al, 2008;Liu et al, 2010aLiu et al, , 2010bAdam et al, 2011;Yu et al, 2011;Liu et al, 2013;Wu et al, 2013;Powikrowska et al, 2014;Hu et al, 2015;Ma et al, 2015;Qi et al, 2015). Constitutive activation of a G-protein a subunit also can suppress the var phenotype (Zhang et al, 2009).…”
Section: Ftshmentioning
confidence: 99%